Ultrasound Backscatter Microscopy for Imaging of Oral Carcinoma. (1st October 2013) - Lam, Matthew; Chaudhari, Abhijit J.; Sun, Yang; Zhou, Feifei; Dobbie, Allison; Gandour-Edwards, Regina F.; Tinling, Steve P.; Farwell, D. Gregory; Monsky, Wayne L.; Shung, K. Kirk; Marcu, Laura
Abstract : Objectives: Ultrasound backscatter microscopy (UBM), or ultrasound biomicroscopy, is a noninvasive, label‐free, and ionizing radiation–free technique allowing high‐resolution 3‐dimensional structural imaging. The goal of this study was to evaluate UBM for resolving anatomic features associated with squamous cell carcinoma of the oral cavity. Methods: The study was conducted in a hamster buccal pouch model. A carcinogen was topically applied to cheeks of 14 golden Syrian hamsters. Six additional hamsters served as healthy controls. A high‐frequency (41 MHz, 6‐mm focal depth, lateral and axial resolutions of 65 and 37 μm, respectively) UBM system was used for scanning the oral cavity after 14 weeks of carcinogen application. Histologic analyses were conducted on scanned regions. Results: The histologic structure of buccal tissue and microvasculature networks could be visualized from the UBM images. Epithelial and mucosal hypertrophy and neoplastic changes were identified in animals subjected to the carcinogen. In animals with invasive squamous cell carcinoma, lesion development and destruction of the structural integrity of tissue layers were noted. Conclusions: In this pilot study, UBM generated sufficient contrast for morphologic features associated with oral carcinoma compared to healthy tissue. This modality may present a practical technique for detection of oral neoplasms that is potentially translatable to humans.